Ceramic Waste Powder as a Partial Substitute of Fly Ash for Geopolymer Concrete Cured at Ambient Temperature - Jay K. Bhavsar; Vijay Panchal (Salehan Institute of Higher Education, 2022)
The growth of the construction industry has expanded the demand for ceramic building products such as ceramic tiles, which constitute essential building materials. Nonetheless, a huge quantity of waste powder is produced during the polishing of ceramic tiles. The disposal of ceramic waste powder is a key environmental concern that needs to be properly addressed. The purpose of this research is to evaluate the potential of recycling ceramic waste powder as a geopolymer binder. The main objective consists of exploring the impacts of two types of ceramic waste powder (vitrified tiles and wall tiles) on the partial substitution of fly ash in geopolymer concrete. For this, concrete was prepared under ambient conditions without oven curing. Slump, compressive strength, split tensile strength, and modulus of elasticity tests were performed to measure the workability and the mechanical properties of the geopolymer concrete. Its durability was evaluated through water absorption and sorptivity tests. The microstructural behavior was investigated using scanning electron microscopy and X-ray diffraction measurements. The investigation revealed that a 15% partial replacement of fly ash by wall-tile ceramic waste powder in geopolymer concrete gave similar compressive strength, a 3% increase in tensile strength, and a 7% improvement in the modulus of elasticity. Partial replacement of fly ash with 15% vitrified ceramic waste powder reduced sorptivity and improved the microstructure of geopolymer concrete. The findings revealed that ceramic waste powder can be used to replace 10–15% of the fly ash in M35 grade structural geopolymer concrete, which can be cured under ambient conditions. Doi: 10.28991/CEJ-2022-08-07-05 Full Text: PDF